(untitled) (Research, Society and Development, 2025)
The female body undergoes countless variations throughout the month and throughout life. In addition, external factors can have an impact on women’s daily lives, such as the choice of contraceptive method. Therefore, an analysis of the consequences of this use is necessary for a good quality of life for this public. The primary objective of this article was to understand the hormonal changes caused using hormonal contraceptives and how this can influence exercise performance in women. This is a literature review study, which analyzed scientific articles, scientific journals, legal documents and demographic census, published between 2002 and 2025, with a thorough reading of abstracts, graphs, tables, research and full articles, the databases used were SCIELO, PUBMED, WHO, IBGE. In this review, brain alterations were found which could influence adherence to training and diets, changes in relation to the level of inflammation in women who used hormonal contraceptive methods, as well as the use of energy substrates differently according to the time of the menstrual cycle or phase of the contraceptive method.